Bringing linguistic research into legal scholarship and practice. (March 2021) - Grey, Alexandra; Smith-Khan, Laura
This article suggests a cohesive articulation of the shared basis upon which the interdisciplinary research field of law and linguistics is developing, organising the research around the familiar three branches of the state: legislature, executive and judiciary, thus providing a map oriented towards non-linguists and legal practitioners. It also invites interdisciplinary scholars to critically reflect on future directions for this research area. This effort to redress the lack of recognition within the law of relevant linguistic research is part of our pursuit of an alternative and more collaborative approach to legal scholarship and law reform addressing issues of communicative barriers and linguistic injustice.